2020
DOI: 10.1002/pbc.28340
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of pathogenic/likely pathogenic germline variants in cancer‐related genes among children with acute leukemia in Saudi Arabia

Abstract: Background:The frequency of pathogenic/likely pathogenic (P/LP) germline mutations in cancerrelated genes among children with cancer in highly consanguineous populations is not well studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…PMS2 mutations have been rare in Lynch syndrome, probably due to difficulties in their identification, but more recently these have been reported, predisposing to endometrial cancer with a relative risk of about twice higher than for colorectal cancer 23 , 25 27 . Recently, PMS2 mutations have been reported also in childhood ALL 21 , 28 . Thus we hypothesize that the associations of ALL with endometrial and rectal cancer may be explained by germline variants in the PMS2 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMS2 mutations have been rare in Lynch syndrome, probably due to difficulties in their identification, but more recently these have been reported, predisposing to endometrial cancer with a relative risk of about twice higher than for colorectal cancer 23 , 25 27 . Recently, PMS2 mutations have been reported also in childhood ALL 21 , 28 . Thus we hypothesize that the associations of ALL with endometrial and rectal cancer may be explained by germline variants in the PMS2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer was one of the associated cancers in families of very young ALL patients, and the Fanconi anemia-BRCA2 pathway is a known risk factor for childhood ALL 2 , 21 . However, if BRCA2 was involved one would expect that ovarian cancer risk was also increased.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that hTERT dysregulation was only observed in limited cases of relapsed childhood ALL [82], while a study in Saudi Arabia disclosed that hTERT mutations are not linked to predisposition to childhood acute leukemia [83]. In terms of relevance in disease pathogenesis, studies have shown that in adult T-cell leukemia/lymphoma (ATLL), the activation of telomerase is required for the disease development and progression, while in AML and CML it is only required for maintenance and not initiation [15,84,85].…”
Section: Tert Dysregulation In Leukemiasmentioning
confidence: 98%
“…Despite the fact that the Saudi Arabia community is considered to be highly consanguineous, no significant correlation was observed between the frequency of P/LP mutations among pediatrics with consanguineous parents compared to those who are not. In addition, the study proposed that homozygous germline mutations in cancer predisposition genes are unlikely to play a substantial role in the risk of childhood leukemia [ 22 ].…”
Section: Reviewmentioning
confidence: 99%